2021
DOI: 10.15243/jdmlm.2021.083.2743
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of biochar and Trichoderma harzianum to promote growth of shallot and remediate lead-contaminated soil

Abstract: This study aimed to determine the effect of biochar and Trichoderma harzianum toward lead removal in soil, lead absorption, lead content in plant tissue also growth and yield of shallot cultivated on lead-contaminated soil. The experimental design used was a completely factorial randomized block design consisting of 2 factors. The first factor was corn cobs biochar which was applied 1 week after basic fertilizer treatment and consisted of 4 levels, namely B0: without biochar, B1: 2.5 t ha-1, B2: 5 t ha-1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…but also performs similar chelating mechanisms to remove HMs from soil [ 19 ]. Herliana [ 22 ] stated that the application of T. harzianum showed the higher adsorption of Pb in soil by intracellular metal immobilization and biosorption of metal ions to cell wall of fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…but also performs similar chelating mechanisms to remove HMs from soil [ 19 ]. Herliana [ 22 ] stated that the application of T. harzianum showed the higher adsorption of Pb in soil by intracellular metal immobilization and biosorption of metal ions to cell wall of fungi.…”
Section: Discussionmentioning
confidence: 99%
“…and sewage sludge biochar was shown to give a significant improvement in soybean dry biomass (70%) and seed germination (20%) relative to control as reported by [ 21 ]. The results of Herliana [ 22 ] showed that the adsorption of Pb was enhanced in soil under the application of organic adsorbents (biochar and T. harzianum ).…”
Section: Introductionmentioning
confidence: 99%